Antenatal detection rate of trisomy 18 & 13 in a teaching hospital from 2002 to 2011. (18th April 2012) - Pathak, S; Smith, RP
Abstract : Background: Trisomy 18 & 13 are the next most common trisomies after trisomy 21, and are usually associated with multiple congenital abnormalities. Currently the national screening programme (FASP)1 only recommends first trimester screening via formal risk calculation for trisomy 21. In practice, first trimester screening will also detect some fetuses with trisomies 18 or 13. The 18-20 +6 week scan will also identify fetuses that may have trisomies 18 or 13. Objectives: We aimed to establish the antenatal detection rate of trisomy 18 & 13 from August 2002 to August 2011 at Norfolk & Norwich University Hospital (NNUH). Methods: All pregnancies or neonates with confirmed trisomy 18 & 13 were identified from the cytogenetics database from August 2002 till August 2011. The detection rate was calculated as the number of cases of trisomy 18 & 13 diagnosed antenatally out of all identified cases who had their antenatal care at NNUH. Results: A total of 68 cases were identified, out of which 18 were referred cases from elsewhere. Of remaining 50 cases, there were 35 cases of trisomy 18 and 15 trisomy 13. Overall, 31 out of 35 cases of trisomy 18 and 12 out of 15 trisomy 13 were diagnosed antenatally, giving a detection rate of 88.6% and 80% respectively. Conclusion: Our detection rate from 2002-2011 was lower than the 95% suggested by FASP. We aim to re-audit in another 5 years following the introduction of the FASP standards in 2010.